EVALUATING THE ACCURACY OF LAND SALES VALUE OF TAXABLE OBJECT DETERMINATION (PBB-P2) THROUGH ASSESSMENT SALES RATIO ANALYSIS - Taufik Wahyu Hidayat (Berkala Akuntansi dan Keuangan Indonesia, 2026)
This research aims to evaluate the accuracy of determining the land Sales Value of Taxable Object (NJOP) of land for the Rural and Urban Land and Building Tax (PBB-P2) in Bantul Regency and to map priority areas for updating NJOP data. A quantitative approach was applied, utilizing both primary and secondary data for analysis. The population comprises all land market transactions in Bantul during 2024, with quota sampling producing 102 samples representing 17 sub-districts. The analysis employed the Assessment Sales Ratio (ASR), including the calculation of the NJOP-to-market value ratio, appraisal level (weighted mean ASR), uniformity measurements using the Coefficient of Dispersion (COD) and Coefficient of Variation (COV), and vertical equity testing through the Price-Related Differential (PRD). The results show that all tax objects have an average ASR of 0.49 and a weighted mean of 0.32, far below the International Association of Assessing Officers’ recommended range of 0.90–1.10, indicating that NJOP values are systematically undervalued. COD and COV values of 49.95 and 51.56, respectively, exceed the acceptable range of 5–25, reflecting a lack of uniformity, while a PRD of 1.52 indicates regressive bias. These findings highlight the need for NJOP reappraisal, prioritizing the sub-districts of Kasihan, Sedayu, Pleret, Bantul, Piyungan, Pandak, and Pundong. The study recommends that local governments adopt ASR analysis as a basis for setting priorities in NJOP updates and for adjusting tax policies to maintain fairness in PBB-P2 liabilities